Comparison of DPD Muslim Electoral Districts of Bali, North Sulawesi, and East Nusa Tenggara in the Perspective of the Powercube Theory - Suswanta, Suswanta; Sulaksono, Tunjung; Sundari, Cici (Journal of Governance and Public Policy, 2023)
This study aims to analyse the comparison of the Muslim DPD in the electoral districts of Bali, North Sulawesi, and East Nusa Tenggara from the Perspective of the Powercube Theory. General election (Pemilu) is the process by which voters elect people to fill certain political positions. Elections are one of the characteristics of a democracy, in which the people are directly involved in selecting leaders and determining the direction of political policies in the next five years. This research method is included in the category of normative research or library research, namely research conducted by examining library materials or secondary data consisting of online media, social media, and journals related to this research by tracing how the explanation of the comparison of the victory of the DPD Muslim Electoral District of Bali, North Sulawesi and East Nusa Tenggara in the Perspective of the Powercube Theory. The analysis technique uses the NVivo 12 plus data processing application, a qualitative document analysis tool with the help of a computer. Their tools are easy to use and can process words and explore word frequencies, attributes, and cases from big data. The results of this study show that the victory of the DPR RI Muslims in the electoral districts of Bali, North Sulawesi, and East Nusa Tenggara is very closely related to the Powercube Theory, where they already have the power of office, both coming from political families and being active in various organisations and have long served the community so they can become members of parliament. As well as having differences and similarities from the background of the actors before serving members of the DPD RI.